2016
DOI: 10.1103/physreve.93.042301
|View full text |Cite
|
Sign up to set email alerts
|

Testing universality in critical exponents: The case of rainfall

Abstract: One of the key clues to consider rainfall as a self-organized critical phenomenon is the existence of power-law distributions for rain-event sizes. We have studied the problem of universality in the exponents of these distributions by means of a suitable statistic whose distribution is inferred by several variations of a permutational test. In contrast to more common approaches, our procedure does not suffer from the difficulties of multiple testing and does not require the precise knowledge of the uncertainti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Coming back to local event-size distributions, recent works have shown that these are indicative of universality as expected in the SOC framework [8][9][10]. The resulting rainevent-size distributions for several sites distributed worldwide are well approximated by power laws of similar exponents over broad fitting ranges, with differences only in the largescale cut-offs of the distributions.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Coming back to local event-size distributions, recent works have shown that these are indicative of universality as expected in the SOC framework [8][9][10]. The resulting rainevent-size distributions for several sites distributed worldwide are well approximated by power laws of similar exponents over broad fitting ranges, with differences only in the largescale cut-offs of the distributions.…”
Section: Introductionmentioning
confidence: 78%
“…For more details, see Ref. [8,10]. The signal directly measured is the rain rate, giving the "instantaneous" depth of precipitation at a point location every minute, with a resolution of 0.001 mm/hour.…”
Section: Rainfall Data and Soc Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are necessary but not 10.1029/2018GL078837 sufficient conditions for SOC to hold. Although recent analysis did not confirm universality for critical exponents of rainfall as may be expected in other phase transitions between ordered (no rain, the off phases) and disordered (rainy or foggy, the on phases) states (Deluca et al, 2016), the SOC paradigm remains a pragmatic model for rainfall description (Pruessner, 2012). A similar analysis of fog events has yet to be conducted so as to understand possible connections between fog and rainfall occurrences.…”
Section: Introductionmentioning
confidence: 99%
“…The first surveys of the intermediate-age clusters, which covered only a small percent of the cluster core areas, did not find any significant population of low-mass members, similar to what was found for the Pleiades. The first studies of the Coma open cluster (age∼ 500 Myr) showed that this cluster has a deficit of low-mass stars in comparison to the younger clusters (Deluca & Weis 1981;Odenkirchen et al 1998). The recent and deeper surveys of this cluster covered a larger field and were reaching into the substellar domain.…”
Section: Introductionmentioning
confidence: 99%